Correlation Of Differentiated Learning Management to Students' Numeracy Literacy Ability in Realistic Mathematics - Nuraida, Ida; Solihah, Sri (Department of Mathematics Education Program IPI Garut, 2025)
Penelitian korelasional ini bertujuan menyelidiki hubungan antara manajemen pembelajaran diferensiasi dan kemampuan literasi numerasi siswa dalam konteks pembelajaran matematika realistik di SMP Negeri 4 Ciamis. Melalui pendekatan deskriptif kuantitatif dengan sampel siswa kelas VII, penelitian mengungkap hubungan signifikan yang sangat kuat antara kedua variabel tersebut. Temuan utama menunjukkan bahwa manajemen pembelajaran diferensiasi memberikan kontribusi sebesar 66% terhadap peningkatan kemampuan literasi numerasi siswa. Hasil analisis statistik memperlihatkan korelasi yang positif dan signifikan, mengindikasikan bahwa implementasi pembelajaran diferensiasi yang efektif berperan penting dalam pengembangan literasi numerasi. Selain itu, penelitian mengidentifikasi faktor-faktor lain yang berkontribusi sebesar 34% terhadap variasi kemampuan literasi numerasi. Kesimpulannya, penelitian ini menegaskan pentingnya penerapan manajemen pembelajaran diferensiasi yang terstruktur sebagai bagian dari strategi untuk meningkatkan literasi numerasi siswa dalam pembelajaran matematika realistik. This correlational study aims to investigate the relationship between differentiated learning management and students' numeracy literacy skills in the context of realistic mathematics learning at SMP Negeri 4 Ciamis. Through a quantitative descriptive approach with a sample of seventh-grade students, the study revealed a powerful and significant relationship between the two variables. The main finding shows that differentiated learning management contributes 66% to the improvement of students' numeracy literacy skills. Statistical analysis results show a positive and significant correlation, indicating that the implementation of effective differentiated learning plays an important role in the development of numeracy literacy. In addition, the study identified other factors that contribute 34% to the variation in numeracy literacy skills. In conclusion, this study emphasises the importance of implementing structured differentiated learning management as part of a strategy to improve students' numeracy literacy in realistic mathematics learning.